General Theoretical Characteristics of the Institution of Disciplinary Liability in Labor Law - A. Yu. Podorozhnii (Bulletin of Kharkiv National University of Internal Affairs)
It has been specified that disciplinary liability should be understood as the employee’s obligation to stand surety to the employer, who is endowed with the disciplinary authority, for his violation of labor discipline in the form of non-performance or improper performance of his labor duties due to the employee and as the result, bear negative consequences provided by labor law.